The Influence of Social Media Language on Students’ Academic Writing in English language education students at Al Mawaddah Warrahmah Islamic Science University Kolaka - Aulia, Andi Nurul; Syahrul, Syahrul (Journal of English Language and Education, 2026)
The widespread use of social media has significantly shaped students’ communication patterns, yet its specific impact on the quality of academic writing remains underexplored, particularly among English language education students in Indonesian tertiary institutions. Addressing this gap, the present study examines how social media language influences the academic writing performance of 10 students in the English Education Department at Al Mawaddah Warrahmah Islamic Science University Kolaka. Data were collected through a questionnaire measuring students’ social media usage and perceptions, alongside an analytical writing task in the form of a short academic essay to identify the presence of informal language features. These features included abbreviations, slang, code-switching, and unconventional punctuation. The findings indicate that frequent social media engagement contributes to the unintentional transfer of informal expressions into academic writing. A total of 31 informal language instances were identified, with Pearson correlation analysis showing a moderate negative relationship (r = –0.42) between social media use and writing accuracy. Despite this, several students reported positive effects such as increased confidence, fluency, and exposure to new vocabulary. In conclusion, social media language exerts a dual influence—diminishing formality and accuracy while enhancing certain aspects of language development. These findings highlight the need for educators to incorporate digital literacy and targeted academic writing instruction to help students manage informal language interference and optimize the benefits of online language exposure.